Soil thermal conductivity estimated using a semi-analytical approach. (May 2021) - Rubin, A.J.; Ho, C.L.
Highlights: A new model to estimate the thermal conductivity of soils was developed to incorporate preferential heat flow. A new database of 124 thermal conductivity measurements on 5 soils at varying density and saturation was produced. The foundation of the new model is a simplified geometry that represents the physical geometry of the three phases of soil structure. The new model was comparable to recent well-functioning existing models. It was observed that models that considered heat transfer flow paths had smaller errors at low saturations than empirically derived models. Abstract: Estimation of soil thermal conductivity is important for many practical geotechnical and civil engineering applications including the thermal performance of buried pipelines, geothermal heat pumps, ground freezing, etc. A significant number of empirical-fit methods to estimate the thermal conductivity of sands exist in the existing literature. This paper provides a semi-analytical approach to estimating the thermal conductivity of soils. The analytical model was developed and validated using existing databases of thermal conductivity. The new model was then compared to select existing models using a new database of thermal conductivity measurements collected for this study on a wide range of soils.